2014
DOI: 10.1016/j.apcatb.2014.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Ultraselective low temperature steam reforming of methanol over PdZn/ZnO catalysts—Influence of induced support defects on catalytic performance

Abstract: The influence of the calcination atmosphere of ZnO precursor (Zn4(CO)3(OH)6·H2O) on the catalytic performance of a series of PdZn/ZnO catalysts was studied for production of H2 via low temperature (180 • C) direct methanol steam reforming (low temperature-MSR). The catalytic activity and selectivity of PdZn/ZnO were found to be strongly influenced by the calcination atmosphere of ZnO precursor and increased from oxidizing to reducing atmosphere, following the order (O2 < air < N2 < H2). As a result, a very act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 54 publications
8
30
0
Order By: Relevance
“…The binding energies are in good agreement to literature [19,36,41,42]. While Iwasa et al [7,13] reported a shift in the Pd 3d 5/2 signal of 0.1 eV by reduction of a 10 wt.% Pd/ZnO catalyst from RT to 493 K, attributed to metal-support interaction, and of further 0.6 eV to 335.9 eV between 573 and 673 K reduction, Zsoldos et al [14] reported an increase of the binding energy by 1 eV to 335.85 eV in between 420 and 880 K reduction of a 8.5 wt.% catalyst.…”
Section: Xpssupporting
confidence: 89%
See 1 more Smart Citation
“…The binding energies are in good agreement to literature [19,36,41,42]. While Iwasa et al [7,13] reported a shift in the Pd 3d 5/2 signal of 0.1 eV by reduction of a 10 wt.% Pd/ZnO catalyst from RT to 493 K, attributed to metal-support interaction, and of further 0.6 eV to 335.9 eV between 573 and 673 K reduction, Zsoldos et al [14] reported an increase of the binding energy by 1 eV to 335.85 eV in between 420 and 880 K reduction of a 8.5 wt.% catalyst.…”
Section: Xpssupporting
confidence: 89%
“…With increasing temperature the water peak shows a shoulder due to the drying effect. Until the end of the temperature program (723 K), a continuous amount of water is detected that can be ascribed to spill-over reduction of the zinc oxide support surface [36], while only a very smooth increase of the water signal could be detected at 671 K (C). In order to better work out the temperature dependence of possible processes like alloy formation or the formation of reduced zinc oxide species (SMSI), the measurements have been repeated with the milder reducing agent CO (A, B), showing a more nuanced reduction profile.…”
Section: Chemical and Structural Behavior Of The System During Reductmentioning
confidence: 99%
“…The obtained results clearly indicate a Pt-catalyzed ZnO reduction, which serves as a reliable sign of the reactive metal (Pt)-support (ZnO) interactions. This is in line with the reported literature suggesting similar catalytic ZnO reduction over Pt and Pd [34,35].…”
Section: Catalyst Characterizationsupporting
confidence: 92%
“…Thus CO 2 was likely to be activated by the generated vacancies and the Cu phase at the interface assisted molecule rearrangement (formate) and hydrogenation to methanol [101] Cu-ZnO Nanorods filament-like The stronger Cu-ZnO interaction and more oxygen vacancies caused by the more exposure of (002) polar face [102] Cu-ZnO Nanotubes High surface area leads to an excellent CO 2 conversion; the high surface mobility of Cu results in low methanol selectivity [103] Methanol steam reforming Cu-ZnO Nanorods The large surface area enhances Cu dispersion, offers an effective surface contact between reactants and catalysts and enhances SMSI [113] Pd-ZnO Nanorods The morphology controlled ZnO not only acts as the support and Zn source for Pd-Zn alloy, but also facilitates one of the intermediate formation steps in MSR [114] Pd-ZnO Needle-like Exposure of ZnO non-polar facet will influence Pd-Zn structure and particle size to influence product selectivity [13] Pd-ZnO Nanoplate Plate-like ZnO possesses the lowest activation energy that leads to the highest specific activity [117] Pd-ZnO Nanoballs assembled by nanosheets Higher oxygen vacancy concentration results in the high H 2 selectivity in MSR reaction [118] Combined reforming hydrogenolysis of glycerol NiMo-ZnO Nanodisk, Nanorods CO 2 adsorbed on the (100) non-polar plane can make the un-occupied Zn cations more electron-deficient, enhancing the Lewis acidity of the non-polar plane [11] Bio-diesel production ZnO Multi-level tower Multi-level tower ZnO predominantly exposed active O 2− on (0002), (1010), (1100) and (0110) facets shows strong basic sites that results in obvious enhancement of catalytic activity and high yield of bio-diesel [124] Bio-ethanol conversion ZnO Needle-like, Flake-like H 2 O was strongly adsorbed on ZnO (001)/(001) polar facets which prohibits the formation of the oxygen vacancy and thus adsorption/dissociation of H 2 O, leading to high ethanol conversion rate but low acetone selectivity. Acetaldehyde reaction to form acetone via the ketonization pathway mainly occurs on the ZnO (100) non-polar facet on which water dissociation is highly favored [129] Ethanol conversion ZnO Brick, Disk, Needle prism The presence of acidic hydroxyl groups on polar surface seems to be responsible for the formation of ethylene and condensation products.…”
Section: Other Thermo-catalytic Reactionsmentioning
confidence: 99%